PERLINDUNGAN HUKUM TERHADAP DEBITUR YANG KESULITAN UNTUK MEMENUHI KEWAJIBAN DALAM PERJANJIAN KREDIT AKIBAT PANDEMI COVID-19 - Hardiansyah Hardiansyah (Dinamika, 2021)
ABSTRACTCorona Virus 2019 has a significant impact on society, especially in the economic sector. In the economic sector, the Financial Services Authority (OJK) issued Financial Services Authority Regulation Number 11 / POJK.03 / 2020 to help debtors who have difficulty fulfilling obligations in credit agreements. This research aims to: 1) look at the background of the issuance of the Financial Services Authority Regulation Number 11 / POJK.03 / 2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of the Corona Desease Virus 2019, 2) to see the form of legal protection for debtors who have difficulty fulfilling obligations in credit agreements before and after the COVID-19 pandemic. The research method in this research is normative juridical. It is known that the background for the issuance of POJK Number 11 / POJK.03 / 2020 is differentiated based on philosophical, juridical, and normative reasons. Then, the form of legal protection provided by the Government to debtors is differentiated during the period before the COVID-19 pandemic and during the implementation of the COVID-19 pandemic.Keywords: Debtor, COVID-19, RestructuringABSTRAKCorona Virus Desease 2019 memberikan dampak yang signifikan bagi masyarakat, khususnya terhadap sektor ekonomi. Pada sektor ekonomi, Otoritas Jasa Keuangan (OJK) mengeluarkan Peraturan Otoritas Jasa Keuangan Nomor 11/POJK.03/2020 untuk membantu debitur yang kesulitan memenuhi kewajiban dalam perjanjian kredit. Penelitian ini bertujuan untuk: 1) mengetahui latar belakang dikeluarkannya Peraturan Otoritas Jasa Keuangan Nomor 11/POJK.03/2020 tentang Stimulus Perekonomian Nasional sebagai Kebijakan Countercyclical Dampak Penyebaran Corona Virus Desease 2019, 2) untuk mengetahui bentuk perlindungan hukum terhadap debitur yang kesulitan untuk memenuhi kewajiban dalam perjanjian kredit sebelum dan setelah adanya pandemi COVID-19. Metode penelitian dalam penelitian ini adalah yuridis normatif. Diketahui yang menjadi latar belakang dikeluarkannya POJK Nomor 11/POJK.03/2020 dibedakan berdasarkan alasan filosofis, yuridis, dan normatif. Kemudian, bentuk perlindungan hukum yang diberikan oleh Pemerintah terhadap debitur dibedakan pada masa sebelum terjadinya pandemi COVID-19 dan pada saat terjadinya pandemi COVID-19.Kata Kunci: Debitur, COVID-19, Restrukturisasi